The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1115/1.4023470
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Algorithm Optimization of a High-Pressure Turbine Vane Pressure Side Film Cooling Array

Abstract: The following work is an in-depth investigation of the heat transfer characteristics and cooling effectiveness of a full-scale fully cooled modern high-pressure turbine (HPT) vane as a result of genetic algorithm (GA) optimization, relative to a modern baseline film cooling configuration. Individual designs were evaluated using 3D Reynolds-averaged Navier–Stokes (RANS) computational fluid dynamics (CFD) that modeled film cooling injection using a transpiration boundary condition and evaluated 10 cells from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…In the present study, the cooling optimization has been done based on the Genetic algorithm (GA). For film cooling applications, satisfactory solutions can be given quickly by GA [20,24]. Darwin's theory of evolution is the motivation of the Genetic algorithms.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, the cooling optimization has been done based on the Genetic algorithm (GA). For film cooling applications, satisfactory solutions can be given quickly by GA [20,24]. Darwin's theory of evolution is the motivation of the Genetic algorithms.…”
Section: Resultsmentioning
confidence: 99%
“…Lee and Kim [19] used coupling Kriging model and sequential quadratic programming to optimize a shaped hole. Johnson et al [20] applied the genetic algorithm to optimize the film cooling array of a high-pressure turbine on the vane pressure side. A multi-objective technique is performed by Lee et al [21] to optimize a shape of one row of fan shape holes.…”
Section: Introductionmentioning
confidence: 99%
“…By means of statistical analysis, they tried to identify the most influencing parameters among blowing ratio, density ratio, hole pitch and trench depth to diameter ratio for a round hole embedded in a trench. Johanson et al [37] went some steps beyond parametric study and used Genetic Algorithm to optimize a high-pressure turbine vane pressure side cooling. They showed that by means of an efficient form of CFD an improved film cooling array could be redesigned from a baseline case.…”
Section: Computational Fluid Dynamics Studiesmentioning
confidence: 99%
“…Johnson et al. 3 performed a GA optimization of a nozzle guide vane. The objective was to minimize the heat load on the vane pressure side by redistributing arrays of cooling holes across the surface as well as varying injection angle, compound angle, and cooling hole area.…”
Section: Introductionmentioning
confidence: 99%